TEACHERS AND STUDENTS’ MOBILITY: A CASE OF STUDY IN THE CONTEXT OF THE INTERNATIONALIZATION OF EDUCATION - Silvia Morresi; Silvina Elías; Ana Carolina Marcos (European Scientific Journal, ESJ, 2014)
Over the last years most countries have been immersed in a process of globalization that has given rise to a growing interdependence between societies as well as a strengthening of international relations both in the economic-financial and in the political and communicational levels.New societies are emerging where structural reforms associated to the process of deregulation and liberalization caused deep changes in work relations. These changes became apparent in the need for growing levels of education and training to gain access to a job and in the growth of importance of the service sector in the structure of production. In this context knowledge is one of the most efficient and dynamic productive inputs, laying the foundations of a new world economy based on information and knowledge, and thereby making education a vital component for the generation and transmission of education. Historically, education has evolved hand in hand with socio-technological changes. Nowadays, progress in information-technology and communication promote a new educational paradigm, whereby the search for quality, pertinence, and internationalization in higher education has a prominent place. The goal of this paper will be to present some indicators to analyze the evolution of the process of internationalization of education in the Department of Economics of the National University of the South (Universidad Nacional del Sur).